ENSINO DE FÍSICA NUCLEAR COM ENFOQUE CTS POR MEIO DA EXPERIMENTAÇÃO - Boch, Layara Baltokoski (2018)
This research had the objective of verifying if a methodology with Science, Technology and Society (STS) approach can contribute effectively to the teaching of Nuclear Physics. To accomplish this aim, a series of lectures on Radioactivity and its Technologies was developed and applied to a group of Youth and Adult Education (YAE) in a private educational institution located in the city of Guarapuava - PR. The research was qualitative and the methodology used was action research. Data collection was through audio recording, questionnaire and annotations, which were evaluated through Discursive Textual Analysis (DTA). With this analysis, eight categories were established, showing that the sequence of classes promoted integration among science, its emerging technologies and society. In their speeches the students presented reflections on the use of radioactivity in the development of technologies, on how this contributed to the improvement in the current quality of life, as well as the consequences for society generated by the misuse of it. They also discussed how political decisions influenced the application of this and other sciences and the importance of information and scientific knowledge for the formation of a participant and conscious society. From the sequence of classes two activities were essential to reach the objective of the research, namely the investigative experimental activity using the electroscope, and the debate. The experimental activity used the electroscope, an instrument of great importance in the history of radioactivity, since it was used by Marie Curie, Rutherford, Geiger and others, in their initial research on the subject. This activity provided subsidies to work on fundamental scientific concepts, on the History of Science, on how scientific research was done at the time, and also allowed to discuss critically about the commercialization of objects that have radioactivity. The debate, in turn, allowed to approach the radiation technologies in general, seeking the understanding of the science that underlies them, as well as the relations of science and technology with society, evidencing the impacts generated, both the positives and the negatives. Thus, the proposed approach contributed to teaching Nuclear Physics and also to forming critical and conscious citizens about science and technology.